2022
DOI: 10.1002/ptr.7357
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of non‐psychoactive Cannabis sativa L. extracts, in vitro antiproliferative activity and induction of apoptosis in chronic myelogenous leukaemia cancer cells

Abstract: In this study, extracts from non‐psychoactive Cannabis sativa L. varieties were characterized by means of ultra high‐performance liquid chromatography coupled with high‐resolution mass spectrometry (UHPLC‐HRMS) and their antiproliferative activity was assessed in vitro. The human chronic myelogenous leukaemia cell line K562 was chosen to investigate the mechanism of cell death. The effect on the cell cycle and cell death was analysed by flow cytometry. Proteins related to apoptosis were studied by western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Even though several researches defined the CBD-mediated anti-proliferative activity in cancer cell lines through the action on its putative endogenous receptors CB1 and CB2 and on GPR55 or TRPV1 [ 27 ], the exact molecular mechanism of action of this compound is still unknown. Recent interesting studies have demonstrated that CBD can inhibit the proliferation of human chronic myelogenous leukemia K562 cancer cells by inducing apoptosis, together with a drop of the mitochondrial membrane potential and the stimulation of caspase 3 and 7 [ 14 ]. Remarkably, the protein expression levels of the above-mentioned receptors were low or absent in the K562 cell line as far as regard the CB2 and thus they cannot be accountable of the antiproliferative activity of CBD ( https://www.proteinatlas.org ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though several researches defined the CBD-mediated anti-proliferative activity in cancer cell lines through the action on its putative endogenous receptors CB1 and CB2 and on GPR55 or TRPV1 [ 27 ], the exact molecular mechanism of action of this compound is still unknown. Recent interesting studies have demonstrated that CBD can inhibit the proliferation of human chronic myelogenous leukemia K562 cancer cells by inducing apoptosis, together with a drop of the mitochondrial membrane potential and the stimulation of caspase 3 and 7 [ 14 ]. Remarkably, the protein expression levels of the above-mentioned receptors were low or absent in the K562 cell line as far as regard the CB2 and thus they cannot be accountable of the antiproliferative activity of CBD ( https://www.proteinatlas.org ).…”
Section: Discussionmentioning
confidence: 99%
“…For the following Western blot experiments performed on protein extracts obtained from K562 cell line, cells were treated for 24 h with CBD 20 μM, corresponding to the IC 25 as optimized by Ref. [ 14 ]. Proteins from both the control and the treated K562 cancer cell line were obtained by lysing and homogenized (in ice) the samples in RIPA buffer with 2 mM phenylmethylsulfonyl fluoride (Merck Life Science S.r.l., Italy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analgesic therapy for psoriasis, antidepressant, bone stimulant, Antiinflammatory [39][40][41][42] Other naturally occurring cannabinoids produced from Cannabis sativa are categorized into a variety of groups, including Cannabidiol (CBD), Cannabichromene (CBC), Cannabicyclol (CBL), Cannabitriol (CBT), Cannabielsoin (CBE), Cannabinol (CBN), and other unconventional types [43]. Cannabinoids interact with several receptors to exert their wide range of beneficial biological effects in the central nervous system and modulate the toxicity of ADassociated proteins.…”
Section: (Cbga)mentioning
confidence: 99%
“…The global CBD oil extract market was valued at US$ 7.94 billion in 2021 with a prospect of reaching US$ 37.74 billion in 2029 [ 12 ]. The increasing popularity of CBD may be attributed to its multiple medicinal properties, all of which have not yet been proven, including antiemetic, antioxidant [ 13 – 16 ], anticancer [ 9 , 17 , 18 ], regenerative [ 10 , 19 , 20 ], and anti-inflammatory [ 21 ] effects. CBD has been tested in therapies for cancer, epilepsy, pain, inflammation, and psychiatric disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%